Clinical Management of Hypothyroidism Associated Dermatological Signs in a Labrador: A Case Report - Das, Gunajit; Deka, Pubaleem; Dutta, Kongkon Jyoti (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Hypothyroidism is the most frequently noticed clinical endocrinopathy in dogs resulting from a loweredproduction and release of T4 and T3 hormones by the thyroid gland (Nelson and Couto, 2014).